Creating Worlds For Music To Exist: How Women Composers of Electroacoustic Music Make Place For Their Voices - McCartney, Andra (Université York, 1995)

Inventing Images: Constructing and Contesting Gender in Thinking about Electroacoustic Music - McCartney, Andra (Leonardo Music Journal, 1995)
The author explores symbolic imagery in the world of electroacoustic music, as presented in both popular music publications and the language of 14 Canadian women composers. While mainstream discourse uses imagery that emphasizes power and control, these composers use metaphors of painting, dancing, sustenance, addiction, wilderness, meetings, circuitry, curses, locks, boxes, blessings and desire to describe their work. This imagery suggests different ways for artists to think about their interaction with technology.

Le rapport inconnu. Quatorze femmes canadiennes dans le studio d'électroacoustique. Seconde partie : compositrices de Montréal et Waterloo - McCartney, Andra (Contact!, 1996)
Keywords: Pas de lien web